LOOP TECHNIQUE: DYNAMICS OF METAL/MELT EQUILIBRATION - Borisov A. (My University, 2001)
I report here the experimental results on the dynamics of equilibration of silicate melts suspended from Ni loops of different diameters at 1400°C and at constant oxygen fugacity. It is found that saturation of silicate melt of anorthite-diopside eutectic composition with Ni is reached during the first few hours because the nickel ions in the melt diffuse extremely rapidly. Fast convection usually results in relatively homogeneous Ni content throughout the sample for loops with diameters 3.2–4.0 mm. Hence, glass homogeneity with respect to an element of interest may not be sufficient evidence that metal/melt equilibrium is reached. It is demonstrated that central parts of Ni diffusion profiles in samples with diameter as low as 2.6 mm are also “flattened” by convection. Possible driving forces of convection in a loop sample are discussed.